Implementasi Sistem Database Terdistribusi Dengan Metode Multi-Master Database Replication - Ahmad Heryanto; Albert Albert (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Databases are the main need for every computer application to store, process and modify data. One important problem faced in databases is the availability of adequate information technology infrastructure in managing and securing data contained in the database. Data stored on the database must have protection against threats and disturbances. Threats and disruptions can result from a variety of things, such as maintenance, data damage, and natural disasters. To anticipate data loss and damage, replication of the database system needs to be done. The replication mechanism used by researchers is multi-master replication. The replication technique is able to form a database cluster with replication time of fewer than 0.2 seconds.